Adaptive partitioning approach to self‐sustained smart grid. Issue 2 (1st January 2017) - Jia, Youwei; Lai, Chun Sing; Xu, Zhao; Chai, Songjian; Wong, Kit Po
Abstract : Effective network partitioning becomes an essential step to realise self‐sustained smart grid, which serves as a prerequisite for 'self‐healing' enabled decentralised control. Splitting the power network (PN) into areas is the last resort to avoid the spread of disruption and to maintain as many network survivals as possible. This study aims to resolve the issue of multi‐objective PN partitioning by deploying a newly proposed hybrid approach concerning both real power balance and voltage profile. The proposed approach combines the Laplacian spectrum and self‐organising map, which adaptively attains self‐sustained network partitions on different operating conditions. The resultant partitions are characterised by the minimal intra‐area real power imbalance with a healthy voltage profile. The authors experimentally evaluate the partitioning effectiveness and computational efficiency in several case studies including on the New England 39‐bus, IEEE 118‐bus, and Polish 2383‐bus transmission systems.